Rumours [videorecording (DVD)] - Maddin, Guy, 1956-; Johnson, Evan, 1983-; Johnson, Galen; Blanchett, Cate, 1969-; Dupuis, Roy, 1963-; Amuka-Bird, Nikki, 1976-; Dance, Charles; Hira, Takehiro, 1974-; Ménochet, Denis, 1976-; Ravello, Rolando; Buric, Zlatko, 1953-; Vikander, Alicia, 1988-; et al. (Decal, 2024)
Follow leaders of the world's wealthiest democracies at the annual G7 summit as they attempt to draft a provisional statement regarding a global crisis: a giant brain leading hordes of menacing bog men.